Peningkatan Kualitas Sumber Daya Manusia Melalui Taman Baca Masyarakat - Agustina Sofiatul Uyun; A. Bachrun Rifa’i; Luk Luk Atin Marfuah (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
In improving the quality of human resources. Human Resources quality must be enhanced through non-formal education by Ambu Seba with Taman Baca Masyarakat (TBM). The existence of Taman Baca Masyarakat as one of the informal educations is expected to help the locals becoming good-quality human resources. The purpose of this study is to identify the role of TBM in improving the quality of human resources, the implementation of the program activities, and the result is improving the quality of Human Resources. The research method used is a descriptive method with a qualitative approach. Type of case study data was collected through interviews, observation, and documents. The result of this study are showing that Taman Baca Masyarakat of Ambu Seba has four roles in improving the quality of Human Resources, which is the facilitator, motivator, local study source, and self-improvement source.